Efficacy and Safety of the Ketogenic Diet for Mitochondrial Disease With Epilepsy: A Prospective, Open-labeled, Controlled Study - Huang, Lijuan; Li, Hua; Zhong, Jianmin; Yang, Liming; Chen, Guohong; Wang, Dong; Zheng, Guo; Han, Hong; Han, Xiong; Long, Yiqin; Wang, Xu; Liang, Jianmin; et al. (Frontiers in Neurology, 2022)
Background: Patients with mitochondrial disease tend to suffer from seizures. Ketogenic diet (KD) is increasingly used to treatment epilepsy because of the favorable effect on seizure reduction. This study was to test the efficacy of KD for mitochondrial disease patients in a controlled trial. Method: Patients diagnosed mitochondrial disease from 14 clinical centers were semi-randomized to intervention (KD) group or control group. KD group followed a 3-month KD intervention, while control group received one-month normal diet at first and then a 3-month KD intervention. The primary outcome was seizures reduction. Biomarker changes, cognition imprisonments and side effects were also recorded if available. Result: A total 33 patients were assigned to KD group (n=22) and control group (n=11). In KD group, 31.8% (7/22) patients achieved ≥50% seizure reduction after one month diet intervention, and increased to 40.9% (9/22) at 3 months. In control group, only 18.2% (2/11) patients had reduction of seizure frequency ≥50% during normal diet period. After control group transferred to KD, 63.6% (7/11) patients had more than 50% seizure reduction, and this rate increased to 72.7% (8/11) at 3 months. KD also showed high efficacy in patients with MELAS and pathogenic variant in mtDNA (90% and 93.3% responder rate respectively). The most frequent side-effects reported at 3-month review were vomiting, cold, hyperlipoidemia and bloating. Conclusion: KD was a safe and effective therapy for seizures control in mitochondrial disease, especially MELAS and pathogenic variant in mtDNA. KD intervention can be considered more in patient’s managements.